Gingival Disease A Professional Approach for Treatment and Prevention - Eddin Omar Al Ostwani, Alaa (Dentistry, 2019)
Gingival diseases interact with many systemic disturbances and can adversely affect a person's quality of life. Therefore an accurate diagnosis with successful treatment and prevention is necessary to mitigate negative consequences and improve the outcome of dental therapy. This book uncovers the hidden causes of many recurrent gingival and oral illnesses, and helps guide the dental professional to diagnosis. By highlighting the importance of gingival treatment and prevention, and then discussing the correlation between gingival and systemic diseases through an academic and professional approach, the book provides the dental practitioner with precise information for treating and managing difficult cases related to systemic diseases. This volume will help both the dentist and the patient to be more satisfied with dental and gingival therapy.